AUTOMOTIVE CIRCUIT SIMULATION: IMPROVING PRIOR KNOWLEDGE ABILITY AND PRACTICAL SKILL ACQUISITION IN THE VEHICLE BODY ELECTRICAL SYSTEM - Susi Tri Umaroh; Sudirman Rizki Ariyanto; Warju Warju (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2025)
This research aims to analyze the improvement of cognitive and psy-chomotor abilities by integrating ACS (Automotive Circuit Simulation) in learning about vehicle body electrical systems. This research is quan-titative research with a quasi-experimental design with two groups, namely an experimental group and a control group. The data collected was analyzed using quantitative descriptive. The results of this research indicate that there are differences in prior knowledge and the acquisi-tion of practical skills among students who utilize ACS media as a learning tool for vehicle body electrical systems. Recommendations from this research include further integrating ACS into the curriculum, increasing the availability of digital learning resources, and providing additional training for educators to optimize the potential for inde-pendent and interactive learning for students through simulation. Thus, this article proposes an innovative solution to effectively support the development of students' knowledge and skills in the field of vehicle body electrical systems.